2011
DOI: 10.4103/0973-1482.87017
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative analysis of argyrophilic nuclear organizer regions in follicular cyst, keratocystic odontogenic tumor and ameloblastoma

Abstract: The current study suggests that determination of clinical behavior of ameloblastoma in comparison with KCOT and follicular cyst in silver nitrate staining is related to higher proliferation activity and different NORs' distribution pattern. However, further clinical follow-up studies must be performed to prove this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Since KOT had been classified as an odontogenic cyst, several authors have compared cell proliferation between KOT and odontogenic cysts (8,12,13). Although several authors have assessed cell proliferation and apoptosis in the odontogenic epithelium in AM and in the epithelial lining in KOT (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), few studies have compared cell proliferation between these tumors (7,8,11) and no previous study has simultaneously evaluated cell proliferation and apoptotic indexes in AM and KOT, comparing both lesions. Therefore, this is the first study assessing comparatively cell proliferation and apoptosis indexes in AM and KOT, although tissue cell population is controlled by a balance among these processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since KOT had been classified as an odontogenic cyst, several authors have compared cell proliferation between KOT and odontogenic cysts (8,12,13). Although several authors have assessed cell proliferation and apoptosis in the odontogenic epithelium in AM and in the epithelial lining in KOT (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), few studies have compared cell proliferation between these tumors (7,8,11) and no previous study has simultaneously evaluated cell proliferation and apoptotic indexes in AM and KOT, comparing both lesions. Therefore, this is the first study assessing comparatively cell proliferation and apoptosis indexes in AM and KOT, although tissue cell population is controlled by a balance among these processes.…”
Section: Discussionmentioning
confidence: 99%
“…A higher proliferation activity in AM epithelium in relation to KOT epithelial lining has been demonstrated (7)(8)(9), even though opposite results have also been reported (10,11). Several studies have evaluated apoptosis and related apoptotic factors in the odontogenic epithelium of AM and epithelial lining of KOT (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…While the proliferation index and expression of apoptosis‐related proteins in OCLs seems to be quite significant for their clinical behavior (Seifi et al , 2011; Soluk TekkeĆŸÄ±n et al , 2012), interestingly, it has been proposed that immune reactions can to contribute with the proliferation and differentiation of the cystic epithelium (Yanagisawa, 1980; Gao et al , 1988; Piattelli et al , 2002). Accordingly, several researches have been developed focusing the study of different cells of the immune system, as well as cellular receptors and inflammatory cytokines, in an attempt to elucidate the mechanisms involved in the pathogenesis of OCLs (Matthews and Browne, 1987; Gao et al , 1988; Murase et al , 1990; Akhlaghi and Dourov, 1995; Suzuki et al , 2001; Piattelli et al , 2002; de Noronha Santos Netto et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…23 However, the finding of similar mAgNORs in SA and UA is in contrast to previous reports of a statistically higher mAgNOR in SA. [24][25][26] A closer comparison of studies revealed differences in AgNOR quantification criteria, as well in sample size (see Supplemental Table I). One important factor that can explain the different results with regard to cells counted, is that both basal and parabasal cells were considered in our study, whereas Colemann et al 24 quantified only basal cells, Ananthaneni et al 26 did not specify which cells were counted (basal or parabasal), and Seifi et al 25 used different criteria for quantification, considering also AgNORs outside the nucleus, which may explain why they observed much higher values than the other studies.…”
Section: Discussionmentioning
confidence: 99%